Pengaruh Electronic Word of Mouth Melalui Media Sosial Instagram Terhadap Minat Beli Produk Scarlett - Harry Sugih Anugrah; Heppy Millanyani; Galuh Sudarawerti (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This study raises questions about the effect of Electronic Word of Mouth on consumer buying interest, with the aim of contributing to companies in increasing the effectiveness of Electronic Word of Mouth to increase buying interest. This study aims to determine the effect of Electronic Word of Mouth through Instagram social media on Scarlett's purchase intention, with variables of information quality, information quantity, information credibility, information adoption and purchase intention. This research is using quantitative methods and this type of research is causal, researchers distributed questionnaires with the help of google form, namely 400 respondents using an ordinal scale. Sample calculation using the formula from Yamane with probability sampling technique and with simple random sampling type in data analysis this research uses descriptive analysis and PLS-SEM method. The findings of this study reveal that the information quality variable, the information quantity variable, and the information credibility variable significantly and positively affect information usefulness. Then, the information usefulness variable significantly and positively affects information adoption, and the information adoption variable significantly and positively affects purchase intention. This research is where the variable that has a high assessment is the information usefulness variable on information adoption.